How to Evaluate the Free Sugars' Content of a Food Product in Europe? Developing and Testing the Reproducibility of a New Method (FS02-08-19). (13th June 2019) - Privet, Lisa; Bougrat, Apolline; Michel, Lisa; Maillot, Matthieu; Chanson-Rolle, Aurelie; Azais-Braesco, Véronique
Abstract: Objectives: Lowering dietary intakes of free sugars is currently promoted by several authorities worldwide. However, the free sugars' content of food is today not readily available on food packaging or food composition tables. The aim of this work was to develop and test the reproducibility of a new methodology to evaluate the free sugars' content of packaged foods sold in the European market. Methods: The new methodology is an 8-step algorithm, consisting of a series of sequential questions based on the information available on packaging. This includes nutrition declaration and list of ingredients, both of which are mandatory on any pre-packaged food sold in the European Union. This method has been tested by eight trained nutritionists on a selection of 37 packaged food products, twice with a 6-week interval. Inter-and intra-individual variability in the estimated free sugar values were studied by linear regression, analysis of variance and principal component analysis. Results: Correlation coefficients between users and sessions for estimated free sugar contents of the 37 selected products were highly significant and above 0.965. When available, the free sugar values provided by the manufacturer, considered to be the true values, were always lower than the estimates generated with the algorithm, in line with the prerequisite of maximizing the free sugars' content in case of uncertainties. In terms of amounts of free sugars, the algorithm performed better than the World Health Organization's method (i.e., provided a value closer to the true value) in 50% of cases; performance was equal in 20% and worse in 30% of cases. Variation coefficients were not dependent on the mean value of estimated free sugars or on the session, but were higher for mixed dishes and composite products (0.942 and 0.193 on average for pooled sessions, respectively) than for other food categories (below 0.09 on average). Finally, there was a user effect, which may come from selecting different steps in the algorithm, a situation that may be limited by improving instructions or training to users. Conclusions: With optimization, this new method shows potential to inform about free sugars' content of individual food products, even those closely related, and could be used for monitoring at the product level. Funding Sources: No funding has been received from external sources for this study.